Ophichthus kailashchandrai sp. nov. (Anguilliformes: Ophichthidae): a new species of snake eel from Indian waters, Bay of Bengal - Mohapatra, Anil; Ray, Dipanjan; Mohanty, Swarup Ranjan; Mishra, Subhrendu Sekhar (Zootaxa, 2020)
A new snake eel (Anguilliformes: Ophichthidae: Ophichthinae) species, Ophichthus kailashchandrai sp. nov., is described from three specimens, collected from the Shankarpur fishing harbour located on the northern part of the Bay of Bengal, West Bengal, India. Ophichthus kailashchandrai sp. nov. is distinguished from its congeners by having its dorsal-fin origin at the posterior third of the pectoral fin, preanal length 2.6–2.8 in TL, uniserial maxillary and mandibular teeth and vertebral count (predorsal vertebrae 14–15, preanal vertebrae 54–55, and total vertebrae 180–182).